RESPONS PADI INPARI TERHADAP MUTAGEN SODIUM AZIDE - Yugi R Ahadiyat; Armida Triani; Siti Nurchasanah (Politeknik Negeri Lampung., 2021)
The objective of this study was to study the response of rice cv. Inpari to soaking time in sodium azide mutagen in terms of sensitivity, seedling performance, and genetic distance based on morphological characters. An experiment was conducted using a split-plot design with rice variety (Inpari 31, 32, and 33) as the main plot, and the soaking time in sodium azide (0, 5, 10, 15, and 20 hours) as the subplot. The result showed that Inpari 32 had more sensitivity, and higher germination and seedling growth performance compared to Inpari 31 and 33. The closest phylogenetic relationship occurred between Inpari 31 and 33 without mutagen, and between inpari 32 and 33 with a soaking time of sodium azide 10 and 20 hours